Establishing long-term partnership to achieve effective partnering. Is it necessary? - Suhaini Muda, (Penerbit Universiti Kebangsaan Malaysia, 2018)
One of the issues in sustaining collaborative partnerships involves the drivers of change and transformation in the process. In particular to this study, various factors have gradually transformed the collaborative partnership activities in the quest for sustaining the collaborative efforts to empower children in orphanages. The paper seeks to explain one of the factors considering the significant discussion among the stakeholders regarding their perspectives on whether long-term partnership is valuable. Using a qualitative case study design, this study uses two methods of data collection with interview as the main method, supported by document review. The data collected were analysed thematically and the findings from the interviews were compared to the findings from documents reviewed. Later the findings are placed alongside the findings of the previous studies from the literature reviewed in the discussions. Based on the interview responses of 24 participants from five stakeholder groups in this collaborative setting and the review of available documents, the findings mainly revealed that partnerships are mostly pragmatics and programme based. Diverse views are given in considering the importance of partnerships to be sustained over a long period in order to be effective. This challenges the common notion that long-term commitment or relationships are needed for effective partnerships.